2014
DOI: 10.1111/cei.12389
|View full text |Cite
|
Sign up to set email alerts
|

Divergent mucosal and systemic responses in children in response to acute otitis media

Abstract: SummaryAcute otitis media (AOM), induced by respiratory bacteria, is a significant cause of children seeking medical attention worldwide. Some children are highly prone to AOMs, suffering three to four recurrent infections per year (prone). We previously determined that this population of children could have diminished anti-bacterial immune responses in peripheral blood that could fail to limit bacterial colonization in the nasopharynx (NP). Here, we examined local NP and middle ear (ME) responses and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…To determine whether there was an intrinsic T-cell defect in sOP children, we stimulated the PBMCs with Staphylococcal Enterotoxin B (SEB) and observed no difference in the percentage of memory CD45RA Low CD4 T cells producing IFN-γ, IL-4, IL-2 or IL-17a in sOP vs. NOP children (see Figure, SDC 1). 21 The results from this study showed that sOP children have suboptimal circulating functional T-helper memory cells after colonization and after AOM and this immune dysfunction contributes to susceptibility to recurrent AOM infections.…”
Section: Adaptive Immune Cell Responsesmentioning
confidence: 69%
“…To determine whether there was an intrinsic T-cell defect in sOP children, we stimulated the PBMCs with Staphylococcal Enterotoxin B (SEB) and observed no difference in the percentage of memory CD45RA Low CD4 T cells producing IFN-γ, IL-4, IL-2 or IL-17a in sOP vs. NOP children (see Figure, SDC 1). 21 The results from this study showed that sOP children have suboptimal circulating functional T-helper memory cells after colonization and after AOM and this immune dysfunction contributes to susceptibility to recurrent AOM infections.…”
Section: Adaptive Immune Cell Responsesmentioning
confidence: 69%
“…pneumoniae colonization in children with an increasing number of episodes of AOM ( P =0.07), a finding that may be spurious, given the multiple tests performed. A previous cross-sectional study of 24 children found no difference between otitis-prone and non-prone children in the nasal expression of IL-17 during AOM [27], whereas an IL-17 receptor knockout mouse model showed higher pneumococcal load in middle ears 3 days after a nasal challenge with S. pneumoniae [28], suggesting that IL-17 expression is an important mediator in the clearance of S.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) A small proportion of children have lower levels of secretory immunoglobulin A or persistent biofilms in the middle ear, which may play a role in increasing the risk for recurrent AOM. (7)(8)(9) There is a clinical spectrum of middle ear infections associated with the initiation and progression of infection leading to bacterial AOM. Middle ear fluid from AOM cases often harbour both viruses and bacteria; however, children who experience spontaneous resolution of AOM are likely to have viral infections alone or to have bacterial organisms that are less virulent (eg, Moraxella catarrhalis and some strains of Haemophilus influenzae) compared with Streptococcus pneumoniae and Streptococcus pyogenes (group A streptococci [GAS]).…”
Section: The Pathogenesis Of Aommentioning
confidence: 99%